ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENINGKATKAN KETAHANAN PANGAN DAERAH DI KABUPATEN SUMEDANG - Ade Opik Rohmanudin; akadun; Rendi Novian (LPPM UNSAP & FISIP UNSAP, 2022)
Utilization of information technology used in providing public services to the community, especially in food security using the internet through information networks. By utilizing this ICT, it can be used to analyze the condition of food in each region, help the public find out information about food security, and be used to manage the distribution of food products and display market information. This study aims to determine how the use of information technology in improving regional food security in the Department of Fisheries and Livestock, Sumedang Regency. This research was conducted using qualitative methods. Data collection techniques were carried out through library research and field studies which included: observation, interviews, documentation studies, and triangulation. Determination of samples/informants in this study was carried out using purposive sampling as many as 4 people. While the data processing procedures used data analysis model Miles and Huberman. The final result of this study concludes that the use of information technology in improving regional food security has been implemented well but not yet optimal. This can be seen from several things, namely the lack of maximum facilities and infrastructure provided to employees, no special application that regulates food, lack of knowledge and ability of employees in using ICT, limited social media accounts owned by the office in providing information about food to the public.